Between the Sordid and the Poetic: An Approach to the Short Stories of Jorge Velasco Mackenzie - Jiménez, Darío (2023)
In the vast collection of short stories by Jorge Velasco Mackenzie (Guayaquil, January 16, 1949-September 24, 2021) one can find different aesthetic and narrative facets focused on human concerns such as the elusive identity of urban metropolis, popular language and characters positioned between conflict and tenderness. His stories belong to a context of Ecuadorian history characterized by the incoherence between economic bonanza and social crisis. In this article, the authors address the form and content that mark some of his most outstanding books of short stories such as De vuelta al paraíso (1975), Como gato en tempestad (1977), Músicos y amaneceres (1988) and Clown y otros cuentos (1988), which confirm the particular style that the author developed throughout his career.